Let Them Be Heard: Bringing Native American Experience Closer in Teaching - Wood, Edyta (Studia Anglica Posnaniensia, 2018)
Teaching about Native Americans, especially as a non-Native person, involves a number of complications. The experience and histories of Indigenous peoples have often been presented from the point of view of the Euroamerican hegemonic power and complicated by a long pattern of colonization, including education. As a result, Native peoples themselves as well as outsiders have been mostly exposed to the dominant culture’s perspectives of Native Americans, often being stereotyped and reductive. The aim of the present paper is to examine the theoretical frameworks advanced by American Indian scholars and educators who demonstrate the methods which expose colonization and show the fundamental Native concepts needed to be involved in the pedagogies concerning Indigenous people. The primary consideration is to be guided by Native peoples' own concepts in trying to avoid perpetuating the colonizing pattern. Bryan McKinley Jones Brayboy (a Lumbee scholar and educator) advanced the Tribal Critical Race Theory, which offers a comprehensive framework which can provide useful guidelines for teaching about Native Americans. The paper also offers suggestions for implementing this framework in the classroom such as using contemporary Native American autobiographical writing, involving the concept of performance or digital resources like those developed by Craig Howe, an Oglala Sioux, and the Center for American Indian Research and Native Studies. Exposing students to Native people through Indigenous people's own stories and resources may be helpful in presenting them as real people. Such an approach may help students to be able to hear and access Native peoples’ own voices sharing their lives, which can contribute to bringing their experience closer to students.